Rechargeable Room‐Temperature Na–CO2 Batteries. Issue 22 (18th April 2016) - Hu, Xiaofei; Sun, Jianchao; Li, Zifan; Zhao, Qing; Chen, Chengcheng; Chen, Jun
Abstract: Developing rechargeable Na–CO2 batteries is significant for energy conversion and utilization of CO2 . However, the reported batteries in pure CO2 atmosphere are non‐rechargeable with limited discharge capacity of 200 mAh g −1 . Herein, we realized the rechargeability of a Na–CO2 battery, with the proposed and demonstrated reversible reaction of 3 CO2 +4 Na↔2 Na2 CO3 +C. The battery consists of a Na anode, an ether‐based electrolyte, and a designed cathode with electrolyte‐treated multi‐wall carbon nanotubes, and shows reversible capacity of 60000 mAh g −1 at 1 A g −1 (≈1000 Wh kg −1 ) and runs for 200 cycles with controlled capacity of 2000 mAh g −1 at charge voltage <3.7 V. The porous structure, high electro‐conductivity, and good wettability of electrolyte to cathode lead to reduced electrochemical polarization of the battery and further result in high performance. Our work provides an alternative approach towards clean recycling and utilization of CO2 . Abstract : Building a better battery : Developing rechargeable metal–CO2 batteries represents a "clean" strategy for advanced energy storage/conversion systems. A rechargeable room‐temperature Na–CO2 battery with superior performance is reported that undergoes the reaction 4 Na+3 CO2 ⇄2 Na2 CO3 +C.